The use of formal education in Denmark 1980-1992 - Christian Hansen (European Regional Science Association (ERSA), 1998)
Education of the labour force is often seen as one of the most important factors for the development of affluent economies. Denmark is such an economy with a GDP per capita above those of Germany and the US. Furthermore inequality is low. Denmark has only 5.1 million inhabitants and is closely interconnected to Cental Europe, both in infrastructure (Border to Germany, and ferry lines to Scandinavia, UK , Germany and Poland) and economically (EU-member since 1973). The Danish economy has been open to im- and export of all kinds of goods for decades. This article analyses the role of formal education for the development of the Danish economy. It uses input-output tables and is based on the Heckscher-Ohlin-Vanek model for trade and factor endowment.
Keywords: 330